Multiple homeostatic mechanisms in the control of P1 plasmid replication - Das, Nilangshu (National Academy of Sciences, 2005)
Many organisms control initiation of DNA replication by limiting supply or activity of initiator proteins. In plasmids, such as P1, initiators are limited primarily by transcription and dimerization. However, the relevance of initiator limitation to plasmid copy number control has appeared doubtful, because initiator oversupply increases the copy number only marginally. Copy number control instead has been attributed to initiator-mediated plasmid pairing (“handcuffing”), because initiator mutations to handcuffing deficiency elevates the copy number significantly. Here, we present genetic evidence of a role for initiator limitation in plasmid copy number control by showing that autorepression-defective initiator mutants also can elevate the plasmid copy number. We further show, by quantitative modeling, that initiator dimerization is a homeostatic mechanism that dampens active monomer increase when the protein is oversupplied. This finding implies that oversupplied initiator proteins are largely dimeric, partly accounting for their limited ability to increase copy number. A combination of autorepression, dimerization, and handcuffing appears to account fully for control of P1 plasmid copy number.